Political Hoaxing!! - Woodward, G. M. (George Moutard), ca. 1760-1809 (Fores, S. W., 1799)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820